2016
DOI: 10.1177/1352458516674367
|View full text |Cite
|
Sign up to set email alerts
|

Age and disability drive cognitive impairment in multiple sclerosis across disease subtypes

Abstract: MULTIPLE SCLEROSIS MSJ JOURNAL1258 journals.sagepub.com/home/msj BackgroundCognitive impairment (CI) is known to be present in all stages of multiple sclerosis (MS); however, the prevalence estimates vary considerably between studies, ranging from 40% to 65%. 1 The profile of CI in the overall MS population is now relatively well known, involving mainly complex attention, information processing speed, episodic memory, and executive functions. 1,2 Therefore, brief neuropsychological batteries for MS 3 and newly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
180
2
20

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 262 publications
(226 citation statements)
references
References 37 publications
24
180
2
20
Order By: Relevance
“…Some studies found a neuropsychological performance impairment in recently diagnosed patients [24, 25], in patients with CIS [7, 26, 27], and in RRMS patients at early stages of the disease with little or no disability [7, 22, 26, 28]. Otherwise, many studies reported a poorer neuropsychological performance in patients with chronic progressive or secondary progressive MS [1, 6, 7, 9] than in RRMS patients. These findings imply that the higher the disability in a more advanced stage of MS, the greater the cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies found a neuropsychological performance impairment in recently diagnosed patients [24, 25], in patients with CIS [7, 26, 27], and in RRMS patients at early stages of the disease with little or no disability [7, 22, 26, 28]. Otherwise, many studies reported a poorer neuropsychological performance in patients with chronic progressive or secondary progressive MS [1, 6, 7, 9] than in RRMS patients. These findings imply that the higher the disability in a more advanced stage of MS, the greater the cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive dysfunction can be detected even at the earliest stages of the disease [6, 7]; nevertheless, its prevalence is higher in chronic progressive patients [7]. Longitudinal studies indicate that CI, if present, progresses over time [4, 8, 9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This analysis was performed adjusting for the effect of age and EDSS that have found to be the independent predictors of CI in a previous analysis of the complete sample. 14 Furthermore, we tested the inclusion of disease duration in the logistic regression models adjusted for age, EDSS and POMS, given that a different disease duration is also expected in patients with POMS and AOMS of the same age.…”
Section: Discussionmentioning
confidence: 99%